2018
DOI: 10.1016/j.jhe.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Delivering affordable housing and neighborhood quality: A comparison of place- and tenant-based programs

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
2
6
0
1
Order By: Relevance
“…Finally, we also use these data to calibrate hedonic models in order to predict the rental value of transactions and social dwellings, which we provide as an additional output of our paper. The estimated rent for social dwellings allows us to document the spatial disparities in the in-kind subsidy received by social tenants in France, which tends to be positively correlated with the income of these households, confirming more systematically previous findings based on local [ 39 , 41 ] or international [ 42 ] studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Finally, we also use these data to calibrate hedonic models in order to predict the rental value of transactions and social dwellings, which we provide as an additional output of our paper. The estimated rent for social dwellings allows us to document the spatial disparities in the in-kind subsidy received by social tenants in France, which tends to be positively correlated with the income of these households, confirming more systematically previous findings based on local [ 39 , 41 ] or international [ 42 ] studies.…”
Section: Discussionsupporting
confidence: 84%
“…As a consequence, the correlation between income and subsidy is smaller within agglomerations. Overall, our results are in line with previous findings in Finland [ 42 ] where it has been shown that social housing are less redistributive than housing allowances as they are harder to concentrate on poorest households.…”
Section: Estimating Hedonic Models For Local French Housing Marketssupporting
confidence: 93%
“…In general, housing policies and programmes are aimed at promoting housing affordability for low-and middle-income households [3][4][5] and at national and regional levels of governments. An adequate housing policy has different intervention mechanisms and strategies that can be utilised to provide housing to low-income households.…”
Section: Introductionmentioning
confidence: 99%
“…Studies are dedicated to the analysis of modern urban dwelling consider the current situation in the housing market and existing problems, but do not fully consider the formation of a new typology as a way to solve them [2][3][4][5][6][7][8]. Within the framework of this study, works related to housing intended for young urban residents are interested in [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%